Disease acceptation and ways of coping with the emotional stress of people after a total hip replacement - Kurowska, Krystyna; Rumińska, Beata (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2011)
Background : Every woman and man wishes themselves life with no disease and stress. Most of people cannot accept the fact of disease. They feel unpleasant emotionally. More seldom they make an effort to change this situation. Aim of the study : The aim of the study was to assess the disease acceptation level and ways of coping with emotional stress of patients who underwent a total hip replacement. Material and methods : 98 patients after a total hip replacement were included in the study. All surgical operations were done at St. Joseph’s County Hospital in Toruń. The disease acceptation was asssessed by means of AIS Juczyński questionnaire and the emotional stress coping questionnaire: the CISS Endler and Parker questionnaire in Polish modification authorised by Szczepanik, Strelau and Wrzesniewski. Results : The members of assessed group reached the average acceptation of disease. The style of coping with the emotional stress which was most often detected in the assessed group was so called task style. More seldom it was – “emotional” and “avoidance” style. The disease acceptation decreased with the increasing of the “emotional” style of coping with the emotional stress. Conclusions : The results can help to prepare better the patient with a total hip, replacement to live with the disease. They also help to plan better the patients treatment. They also allow to start the activity which aims to help in disease acceptation.